Effect of Preplanting Fertilizer, Source and Rate of Postemergence Nitrogen on the Yield and Growth of Dwarf Wheat in the Kufra Oasis, Libya - EL-SHARKAWY, M. A.; SGAIER, K. (The Libyan Journal of Agriculture, 2023)
An investigation was made of the effect of 48 fertilizer combinations on the grain yield, growth and dry matter production of the dwarf wheat Triticum aestivuni L. grown in the sandy soil of Kufra desert. Differences were found among preplanting treatments as well as among postemergence nitrogen levels in grain yield, weight and number of grains/ spike, grain size, total dry weight of plants, dry weight of roots, dry weight of culms, number of tillers and height of plants. The various components of grain yield, plant growth and dry matter production were limited by the soil nutrient status before planting. Efficiency of Urea-nitrogen compared with ammonium sulfate-nitrogen as postemergence application was 39,33,32.6,28.3 and 32.2% for grain yield, nitrogen content in leaves, total dry weight of plants, dry weight of roots and dry weight ofculms, respectively. The addition of postemergence nitrogen from both sources was ineffective in the absence of preplanting fertilizer (phosphorus and nitrogen) in grain and dry matter production.